Promoting Clean Energy Innovation at the State and Local Level. (August 2020) - Popp, David
Abstract: Innovation is an important part of energy policy, and encouraging clean energy innovation is often an explicit goal of policy makers. For local governments, promoting clean energy innovation is seen not only as a pathway to a cleaner economy but also as a tool for promoting the local economy. But is such optimism warranted? There is a substantial literature examining the relationships between innovation and environmental policy, but few studies focus explicitly on innovation at the state and local level. In this paper, I provide key lessons from research on clean energy innovation, focusing on lessons relevant for state and local governments. I then summarize the results of a recent working paper by Fu et al. (2018 ) that studied wind energy innovation across individual states in the United States. While state-level policies can promote clean energy innovation, it is overall market size that matters most. Thus, innovation need not occur in those states most actively promoting clean energy. I conclude with lessons for state and local governments drawn from both this work and the broader literature on energy innovation.